Interest in Lung Screening among a Sample of Adult Muslims in the United States - Attarabeen, Omar; Alkhateeb, Fadi; Larkin, Kevin; Sambamoorthi, Usha; Newton, Michael; Kelly, Kimberly (Iraqi Journal of Pharmaceutical Sciences, 2024)
Objectives. Muslims in the United States exhibit high rates of tobacco use, which make them highly vulnerable to lung cancer. Lung cancer could be avoided by regularly undergoing preventive lung screening. This study investigated the associations between Social Cognitive Theory factors and being interested in preventive lung screening in a sample of adult US Muslims. Methods. We examined a convenience sample of adult US Muslims. A cross-sectional online survey was used to collect data. Binomial logistic regression analyses were conducted to identify the factors related to interest in preventive lung screening. Key Findings. Two hundred seventy-one eligible participants (≥18 years old Muslim individuals who live in the US) from 30 states completed the questionnaire. Individuals were more likely to express an interest in lung cancer screening if they had 1) more positive attitudes about lung screening, 2) a higher perceived value of screening, and 3) greater self-efficacy regarding the ability to undergo lung screening. Conclusion. Addressing attitudes, perceived value, and self-efficacy in future interventions could increase interest in preventive lung screening amongst adult US Muslims.